Does sauna bathing prevent chronic obstructive pulmonary disease or Alzheimer's disease? May adults with cardiovascular disease use a sauna? A systematic review - Maciej Sobczyk; Małgorzata Słaboń; Małgorzata Pasztelan; Jarosław Pulikowski; Karolina Garbacz; Maria Maciąg; Julia Krawczuk vel Walczuk; Joanna Baran; Aleksandra Muca; Aleksandra Marczak (Kazimierz Wielki University, 2024)
Recently, there has been a surge of interest in sauna bathing and its role in health aspects. However, there are few studies focusing on the association between regular sauntering and the risk of dementia and chronic obstructive pulmonary disease (COPD). Considerably better understood are the effects on the cardiovascular system. This study delves into contemporary scientific research on Finnish saunas, exploring their potential correlation with Alzheimer's disease prevention, their impact on vascular health in adults with cardiovascular disorders, and their association with reducing the risk of chronic obstructive pulmonary disease. Scientific studies published in PubMed, Scopus and Google Scholar databases were analyzed, including terms related to Finnish sauna, dementia, COPD and cardiovascular disease. The methodological quality and results of each study were evaluated. Sauna bathing in addition to being a relaxing lifestyle habit, remains a potential additional strategy which can be used in improving cardiovascular function in adults with well-controlled cardiovascular disorders. A limited amount of research has been identified on the correlation between sauna bathing and reduced risk of Alzheimer's disease and COPD. The accumulating evidence suggests that frequent sauna bathing may reduce the risk or severity of several vascular and nonvascular conditions including COPD and also moderate to high frequency of sauna bathing was associated with lowered risks of dementia and Alzheimer's disease. Further research is required, especially large-scale cohort studies with repeated measurement on sauna to establish the potential mechanisms linking sauna bathing and either memory diseases or COPD and better understand the relationship between sauntering and cardiovascular health. Upcoming studies may become very promising for the development of sauna bathing as a new non-pharmacological treatment or prevention of various diseases and improvement in the quality of life.